Working capital management and firm value in emerging markets the case of sri lanka - Pratheepkanth, P. (University of Jaffna, 2020)
Working capital management, which involves managing cash, inventory, and accounts receivable, affects a firm’s short-term attainment. The purpose of this paper is to seek to investigate the relationship between working capital management and firm value in Sri Lankan firms. Data from 100 Sri Lankan firms a period of five years (2014-2018) are used for this purpose and analysed using the regression technique. The results indicate that there is a strong positive relation between the firm’s cash conversion cycle, number of day’s account payable and firm size and its firm value. Although, number of day’s account receivable and number of day’s inventory are found to be significant with negative sign. Overall the results imply that the Sri Lankan firms need to concentrate their limited resources on managing cash conversion cycle in order to be improve firm value.
Keywords: Working capital; Cash conversion cycle; Firm value